2014
DOI: 10.1016/j.aap.2014.01.001
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of fishing vessel accident severity

Abstract: The study examines the determinants of fishing vessel accident severity in the Northeastern United States using vessel accident data from the U.S. Coast Guard for [2001][2002][2003][2004][2005][2006][2007][2008]. Vessel damage and crew injury severity equations were estimated separately utilizing the ordered probit model. The results suggest that fishing vessel accident severity is significantly affected by several types of accidents. Vessel damage severity is positively associated with loss of stability, sink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 5 publications
12
28
0
Order By: Relevance
“…Overturning is a decisive factor in the total loss of a shipwrecked commercial fishing vessel (Jin et al, 2001). Later, Jin (2014) collected the data on ship accidents from the U.S. Coast Guard from 2001 to 2008 and the result showed that the severity of fishing vessel damage was positively associated with destabilization, foundering, daytime wind speed, ship age and distance from the shore. In terms of oil tankers, oil spills seriously damage the marine economy development such as fishery and cause significant damages to marine ecological resources (Aguilera et al, 2010).…”
Section: Literature Overviewmentioning
confidence: 99%
“…Overturning is a decisive factor in the total loss of a shipwrecked commercial fishing vessel (Jin et al, 2001). Later, Jin (2014) collected the data on ship accidents from the U.S. Coast Guard from 2001 to 2008 and the result showed that the severity of fishing vessel damage was positively associated with destabilization, foundering, daytime wind speed, ship age and distance from the shore. In terms of oil tankers, oil spills seriously damage the marine economy development such as fishery and cause significant damages to marine ecological resources (Aguilera et al, 2010).…”
Section: Literature Overviewmentioning
confidence: 99%
“…Yip (2008) employed the negative binomial regression technique to describe the injuries and fatalities caused by ship accidents in Hong Kong Waters. Jin (2014) developed an ordered Probit model to evaluate the vessel damage and crew injury severity in fishing vessel accidents. However, it should be pointed out that the majority of shipping accidents may cause no fatalities or injuries.…”
mentioning
confidence: 99%
“…Hull type and propulsion variables, however, are mostly used in studies examining a specific type of vessel. For example, Jin (2014) and Jin et al (2001) focused solely on fishing vessels in their research on accident severity.
Figure 2.Conceptual framework for the analysis of harbour tugboat accident severity.
…”
Section: Methodsmentioning
confidence: 99%
“…
Figure 2.Conceptual framework for the analysis of harbour tugboat accident severity. References: Talley (1995, 1996, 1999a, 1999b), Jin et al (2001), Talley et al (2006, 2008), Jin (2014), Wang and Yang (2018), Weng et al (2018), Weng and Li (2019).
…”
Section: Methodsmentioning
confidence: 99%